Linking groundwater simulation and reservoir system analysis models: The case for California's Central Valley. (March 2016) - Dogrul, Emin C.; Kadir, Tariq N.; Brush, Charles F.; Chung, Francis I.
Abstract: Groundwater is an important resource. In many developed basins it meets part or all of the water demands. In addition, the management of groundwater resources directly impacts stream flows through stream-aquifer interactions. Yet many reservoir system analysis models that are used for the management of surface water resources either include a simplified representation of the groundwater flow dynamics or rely on surrogate models (linear response functions, artificial neural networks, etc.) which are trained using more complex groundwater models. These approaches may introduce restrictive, sometimes inaccurate, representation of the groundwater flow dynamics and additional modeling steps. In this study a reservoir system analysis model that utilizes an LP solver is linked directly to a non-linear, three-dimensional, finite element groundwater model. The linked model is a general-purpose model and can be applied to any basin. Some of the features of the linked model are showcased by an application to California's Central Valley. Highlights: A groundwater model was directly linked to a reservoir systems analysis model. Nonlinear groundwater flows were simulated within LP-based reservoir systems model. Linked model was applied to California's Central Valley. Effects of groundwater on reservoir operations were examined by a drought scenario. Linked model is generic and can be applied to any basin with no code changes.